Do "barro de loiça" à "loiça de barro": caracterização etnopedológica de um artesanato camponês no Agreste Paraibano - Alves, Ângelo Guiseppe Chaves (Universidade Federal de São Carlos, 2004)
Ethnopedological studies have been devoted mainly to agriculture, paying little attention to other aspects (e.g. pottery) of land use. The main objective of this work was to describe and analyse local knowledge and practices among peasant potters, as related to some soils that they use as ceramic resource, in a rural village (Chã da Pia) in Northeast Brazil. Peasant soil knowledge was described and analysed through an adaptation of classic ethnoscientific techniques, attempting to articulate emic and etic data, following Marques s Comprehensive Ethnoecology. Five soil profiles were formally described by researchers (etic approach) near pits where local people obtain pottery clay. Later, peasant artisans where asked to indicate the soil categories or materials they recognized in those same soil profiles (emic approach). Samples collected during both emic and etic approaches were used to describe and analyse the soils existing near these clay sources. Peasant potters recognized variations between the topsoil and subsurface soil. They were capable of distinguishing, identifying and naming, their way, some soil materials arranged in layers ( capas ) along the soil profile: terra (earth), piçarro (gravel), cabeça do barro (clay head), barro de loiça (ceramic clay), and pedra mole (soft rock). The multi-layered arrangement of these materials along the soil profiles was similar to the arrangement of the horizons as described in formal pedology. Nonetheless, local potters did not seem to know about pedogenetic relationships among these layers. Discriminant-canonical analysis, based on chemical, physical and morphological soil features, has shown clear distinctions between the agricultural topsoil and subsurface layers from where ceramic resources may be collected. It also made possible to demonstrate physical, chemical and morphological similarity among some soil materials (as distinguished by local potters) and the pedogenetic horizons where these materials are normally found. Barro de loiça is the main ceramic resource obtained from local soils. It was found mainly as part of the the 2Bt horizon in Eutric Planosols and Haplic Solonetz. The making of ethnopedological studies in different social and pedological environments could be an aid to the advancement of formal soil knowledge, also giving an opportunity to understanding and valuing local soil knowledge and management.
Keywords: Ecologia humana; Etnoecologia; Etnopedologia; Campesinato; Cerâmica; Planossolos; Ethnoecology; Ethnopedology; Peasantry; Pottery; Planosols; Solonetz; CIENCIAS BIOLOGICAS::ECOLOGIA